Parental Education on Hidden Sugars: A Preventive Strategy Against Childhood Diabetes - Yoni Astuti (CV. Inara, 2026)
Introduction:The increasing incidence of type 2 diabetes in children is a growing public health concern, often linked to excessive consumption of sugar-rich, energy-dense foods. Many of these contain hidden sugars not easily recognized by consumers. As children are especially drawn to sweet tastes, early dietary habits can significantly impact long-term health. Parental knowledge is essential in guiding healthier food choices and preventing early exposure to diabetes risk. This study aimed to enhance parental awareness of dietary sugar intake and its potential role in childhood diabetes. Methods:A quasi-experimental pre-test–post-test design was used to evaluate the effectiveness of a health education intervention. The program included a structured lecture and interactive discussion focusing on hidden sugars and diabetes risk. Knowledge was measured using a validated questionnaire administered before and after the intervention. Data were analyzed using paired t-tests and correlation analysis.Results: The mean knowledge score increased from 7.87 ± 2.03 to 9.65 ± 1.38 (p < 0.001; 99% CI), reflecting a 22.54% improvement. The intervention significantly enhanced parental understanding of hidden sugars.Conclusions: The educational intervention effectively increased parental knowledge regarding hidden sugars and diabetes risk in children. Similar health education programs should be implemented at the community and school levels to support broader diabetes prevention efforts in children.